Empagliflozin alleviates renal inflammation and oxidative stress in streptozotocin-induced diabetic rats partly by repressing HMGB1-TLR4 receptor axis - Zahra Ashrafi Jigheh; Amir Ghorbani Haghjo; Hassan Argani; Leila Roshangar; Nadereh Rashtchizadeh; Davoud Sanajou; Saeed Nazari Soltan Ahmad; Jalil Rashedi; Siavoush Dastmalchi; Mehran Mesgari Abbasi (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): Empagliflozin, a sodium-glucose cotransporter-2 (SGLT-2) inhibitor, possesses verified anti-inflammatory and anti-oxidative stress effects against diabetic nephropathy. The present investigation aims to examine empagliflozin effects on the renal levels of high mobility group box-1 (HMGB1), a potent inflammatory cytokine, and its respective receptor toll-like receptor-4 (TLR-4) in STZ-induced diabetic rats.Materials and Methods: Empagliflozin at 10 mg/kg per os (p.o.) was administered for 4 weeks, starting 8 weeks after the induction of diabetes. Renal function, kidney inflammation, oxidative stress, and apoptosis markers as well as renal HMGB1, receptor for advanced glycation end products (RAGE), and TLR-4 levels were assessed.Results: In addition to down-regulating NF-κB activity in renal cortices, empagliflozin reduced renal levels of HMGB1, RAGE, and TLR-4. It alleviated renal inflammation as indicated by diminished renal expressions of inflammatory cytokines and chemokines like tumor necrosis factor-alpha (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) and also decreased urinary levels of interleukin-6 (IL-6) and alpha-1 acid glycoprotein (AGP). Moreover, empagliflozin ameliorated renal oxidative stress as demonstrated by decreased renal malondialdehyde (MDA) and elevated renal activities of superoxide dismutase (SOD) and glutathione peroxidase (GPX). It also suppressed renal caspase-3, the marker of apoptosis; and furthermore, enhanced renal function noticed by the declined levels of serum urea and creatinine.Conclusion: These findings underline that empagliflozin is able to attenuate diabetes-related elevations in renal HMGB1 levels, an influential inflammatory cytokine released from the necrotic and activated cells, and its correspondent receptors, i.e., RAGE and TLR-4.